Emerging Pathophysiological Targets of Psoriasis for Future Therapeutic Strategies - Yadav, Monu; Sardana, Ishu; Sharma, Amarjeet; Sharma, Nidhi; Nagpal, Kalpana; Malik, Paramjeet (Infectious Disorders - Drug Targets, 2020)
Psoriasis is a chronic autoimmune skin disorder which involves complex interactions between genes, keratinocytes, T-cells and inflammatory cells. It affects 2-3% population worldwide. Molecular biology and cellular immunology of psoriasis, when linked with biotechnology and genetic studies can help researchers to understand the pathophysiology of psoriasis. T-cells activation, keratinocyte hyperproliferation, and angiogenesis are the core mechanisms entailed in the development of psoriasis lesion. Investigators are trying to overcome the challenges of complex pathophysiology pathways involved in this disorder. The different possible hypotheses for its pathophysiology such as growth factors, enzymes, inflammation, and genetic factors mediated pathophysiology have been described in the present review paper in detail. Clinically available drugs only control the symptoms of psoriasis but are not effective for the treatment of the disorder completely and are also associated with some side effects such as itching, renal disorders, hematologic, nonmelanoma skin cancer, pulmonary, gastrointestinal toxicity, etc. This paper made an effort to understand the pathophysiological targets, discuss the research done so far and the treatments available for the effective management of psoriasis.
Keywords: gastrointestinal toxicity